EFNS‐ENS/EAN Guideline on concomitant use of cholinesterase inhibitors and memantine in moderate to severe Alzheimer's disease. (25th March 2015) - Schmidt, R.; Hofer, E.; Bouwman, F. H.; Buerger, K.; Cordonnier, C.; Fladby, T.; Galimberti, D.; Georges, J.; Heneka, M. T.; Hort, J.; Laczó, J.; Molinuevo, J. L; et al.
<x xml:space="preserve">Abstract</x> Background and purpose Previous studies have indicated clinical benefits of a combination of cholinesterase inhibitors (ChEI) and memantine over ChEI monotherapy in Alzheimer's disease (AD). Our objective was the development of guidelines on the question of whether combined ChEI/memantine treatment rather than ChEI alone should be used in patients with moderate to severe AD to improve global clinical impression (GCI), cognition, behaviour and activities of daily living (ADL). Methods A systematic review and meta‐analysis of randomized controlled trials based on a literature search in ALOIS, the register of the Cochrane Dementia and Cognitive Improvement Group, was carried out with subsequent guideline development according to the Grading of Recommendations Assessment, Development and Evaluation (GRADE) system. Results Pooled data from four trials including 1549 AD patients in the moderate to severe disease stage demonstrated significant beneficial effects of combination therapy compared to ChEI monotherapy for GCI [standardized mean difference (SMD) −0.20; 95% confidence interval (CI) −0.31; −0.09], cognitive functioning (SMD −0.27, 95% CI −0.37; −0.17) and behaviour (SMD −0.19; 95% CI −0.31; −0.07). The quality of evidence was high for behaviour, moderate for cognitive function and GCI and low for ADL. Agreement of panellists was reached after the second round of the consensus finding procedure. The desirable effects of combined ChEI and memantine treatment were considered to outweigh undesirable effects. The evidence was weak for cognition, GCI and ADL so that the general recommendation for using combination therapy was weak. Conclusions We suggest the use of a combination of ChEI plus memantine rather than ChEI alone in patients with moderate to severe AD. The strength of this recommendation is weak.